2022
DOI: 10.1186/s12884-022-04471-y
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial colonization at caesarean section defects in women of secondary infertility: an observational study

Abstract: Background Delayed childbearing has been noted in a high percentage of women with a previous Caesarean section (CS). Many women with CS scar defects (CSDs) present with clinical symptoms of irregular vaginal bleeding. The present study aimed to investigate bacterial colonies at CSDs in women suffering from secondary infertility. Methods This observational study included 363 women with secondary infertility who visited the Assisted Reproduction Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…On the current hypothesis, one is that isthmocele might provide a detrimental environment for sperm penetration and embryo implantation (19) by the accumulation of intra uterine uid acting like in other gynecological conditions such as hydrosalpinx ( 13), the increased in ammation within the niche (11,20), the distorted myometrial contractility due to the uterine scar. In a prospective study on 364 women presenting secondary infertility (21), signi cantly more bacteria colonies including among other colonies more Gram neg rods (E.Coli, Pseudomonas Aeruginosa) were found in uterine niche than in patients without a uterine niche or without CS (respectively 89.6%, 69.6% and 49.7%). If we make the analogy with chronic endometriosis (22,23), we might hypothesize that it could in uence IVF results.…”
Section: Discussionmentioning
confidence: 99%
“…On the current hypothesis, one is that isthmocele might provide a detrimental environment for sperm penetration and embryo implantation (19) by the accumulation of intra uterine uid acting like in other gynecological conditions such as hydrosalpinx ( 13), the increased in ammation within the niche (11,20), the distorted myometrial contractility due to the uterine scar. In a prospective study on 364 women presenting secondary infertility (21), signi cantly more bacteria colonies including among other colonies more Gram neg rods (E.Coli, Pseudomonas Aeruginosa) were found in uterine niche than in patients without a uterine niche or without CS (respectively 89.6%, 69.6% and 49.7%). If we make the analogy with chronic endometriosis (22,23), we might hypothesize that it could in uence IVF results.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic progesterone inhibits ovulation. This regulates the menstrual cycle and reduces the risk of bleeding and hormonal fluctuations associated with isthmocele [111]. Additionally, it modifies the thickness of the endometrium, reducing hypertrophy and thickening.…”
Section: Progesterone-releasing Iudsmentioning
confidence: 99%
“…7 According to the histopathology findings mentioned above, chronic inflammation can be considered as a cause. Hsu et al 61 reported that bacterial colonization is more frequent in women with secondary infertility due to CSD.…”
Section: Decre a S Ed Fertilit Y In Women With C S D Imentioning
confidence: 99%
“… 7 According to the histopathology findings mentioned above, chronic inflammation can be considered as a cause. Hsu et al 61 reported that bacterial colonization is more frequent in women with secondary infertility due to CSD. Microorganisms may be present because of the retention of blood in CSD and contribute to chronic inflammation.…”
Section: Decreased Fertility In Women With Csdimentioning
confidence: 99%